ANALISIS WACANA ABSOLUTISME TAUHID PADA KAJIAN GUS BAHA DI KANAL YOUTUBE NU ONLINE - Nur Ahmad El Aufa (STAI Sufyan Tsauri Majenang, 2021)
Communication technology is growing rapidly making the people increasingly easy to access a variety of information. Through the hand, people can increase knowledge, looking for entertainment, and access everything according to the wishes of. Social Media is very popular by the users of internet services around the world, Indonesia is no exception. from the various available social media, Youtube is the most visited social media platform, including in Indonesia. The development of the digital world appears to be welcomed by the activists of da'wah, both individual and institutional. Many da'wah activists who have created Youtube channels to disseminate religious teachings. Not a few Islamic mass organizations who have a Youtube channel for similar stuff. Nahdlatul Ulama for example, has a Youtube channel named NU Online to present islamic studies. One of the studies that is often uploaded by NU Online and watched by many viewers is the lecture of Gus Baha, a rising ulama in the real world and cyberspace. Although Gus Baha is an ulama who affiliated with the Islamic organization Nahdlatul Ulama, the Sultan Agung University research in Semarang reveals that more than 50% of the audience of Gus Baha's study is not Nahdliyyin. The study concluded that Gus Baha became one of the unifying religious figures for Muslims. These factors make the researcher interested to know in detail every message of da'wah conveyed in Gus Baha’s study, and in this research is the message of da'wah containing akidah. Thus, the method used in analyzing the da'wah message on the aspect of faith in this study is Teun Van Dijk's discourse analysis method, because researcher can further examine the study in terms of text, social cognition, and social context.Keywords: Gus Baha, NU Online, Discourse Analysis, Da’wah Message